ANALISIS KAPASITAS KELEMBAGAAN KELOMPOK TANI HUTAN WAKU LANI DESA LENEK DUREN DAN DESA TOYA LOMBOK TIMUR - Lutfia Azizah; Andi Chairil Ichsan; Kornelia Webliana (Jurnal Sylva Scienteae, 2021)
The Waku Lani forest farmer group is a group which is under the management of the Mount National Park Rinjani this group has an institutional capacity not yet optimal. For upgrade capacity the institutional strategy needed to strengthen management institutional. With forestry number 57 of 2014 and Ostrom Theory (1990) to analyze institutional capacity and analysis SWOT to study group strengthening strategies. Method in this study using the interview method, literature observations and studies. Based on research institutional capacity is carried out in the class category beginner with a score of 210 based forestry number 57 of 2014 and institutional performance in the low category with a score of 13 based on the theory Ostrom (1990) this shows that several indicators need to be optimized through a strengthening strategy for increase group institutional capacity. Strategy what is done is to strengthen institutions through capacity building for group dynamics.Keywords : National Park; Institutional, Strategy, Group Dynamic